Productivity in public administration: concept and application in India - Bava, Noorjahan (2000)
The concept of productivity needs to be widened so as to embrace not only its economic aspect (ratio between inputs and outputs) but also the political, administrative, social, cultural, national, international dimensions. Many aspects of public sector productivity are qualitative and do not lend themselves to quantification and measurement. A holistic approach to the problem is a virtual necessity. - Reproduced
Keywords: Public administration - India; Public administration